2009
DOI: 10.1007/s10530-009-9637-7
|View full text |Cite
|
Sign up to set email alerts
|

Investment in seed dispersal structures is linked to invasiveness in exotic plant species of south-eastern Australia

Abstract: Naturalized plant species disperse their populations over considerable distances to become invasive. We tested the hypothesis that this shift from naturalization to invasion is facilitated by increased investment of resources in seed dispersal appendages, using an assemblage of naturalized plants of southeastern Australia. Compared with non-invasive species, we found in both cross-species and independent-contrasts analyses that invasive species invested more heavily in seed dispersal appendages, regardless of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 33 publications
2
32
0
1
Order By: Relevance
“…Thus, ecologists have recently paid special attention to the successful invasion mechanism of those invaders [1][2] -particularly their reproductive allocation strategy (RA, i.e., the proportion of biomass allocated to reproductive structures) [4]. Some invasive plants successfully invade certain environments because those species feature fecundity and high-efficiency multiple reproduction modes [4][5]. Meanwhile, functional traits determine how plants reproduce and gain resources [6], and such traits affect the success of a species in competition with other species for living resources [7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ecologists have recently paid special attention to the successful invasion mechanism of those invaders [1][2] -particularly their reproductive allocation strategy (RA, i.e., the proportion of biomass allocated to reproductive structures) [4]. Some invasive plants successfully invade certain environments because those species feature fecundity and high-efficiency multiple reproduction modes [4][5]. Meanwhile, functional traits determine how plants reproduce and gain resources [6], and such traits affect the success of a species in competition with other species for living resources [7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It has often been suggested that introduced and/or invasive species have greater natural dispersal abilities than do native or less invasive species [14]. For instance Murray and Phillips [1] state that “naturalized invasive species that spread by seed possess enhanced strategies for seed dispersal that are either absent or at least not as prevalent in naturalized species that are not invasive”.…”
Section: Introductionmentioning
confidence: 99%
“…For instance Murray and Phillips [1] state that “naturalized invasive species that spread by seed possess enhanced strategies for seed dispersal that are either absent or at least not as prevalent in naturalized species that are not invasive”. Thompson and Davis [5] state that research on traits of invasive plants “has revealed that, when compared with natives or non-invasive aliens, invasive aliens …produce more seeds that are better dispersed…”, and Ordonez and Olff [4] state that “ analyses comparing regional and global species pools of natives and aliens have found that aliens … .…”
Section: Introductionmentioning
confidence: 99%
“…Natal grass seeds are light; a gram contains from 1,311 to 1,417 (21) . The small weight of the seed and its plumose characteristics are attributes for an efficient and fast dispersion (39,40,41) .…”
Section: Seed Productionmentioning
confidence: 99%
“…Las semillas de rosado son livianas; un gramo contiene de 1,311 a 1,417 (21) . El peso de la semilla y su característica plumosa le confieren atributos para una eficiente y rápida dispersión (39,40,41) .…”
Section: Producción De Semillaunclassified